GAYA KEPEMIMPINAN TRANSFORMASIONAL KOPERASI EPTILU DALAM PEMBERDAYAAN PETANI HORTIKULTURA DI KABUPATEN GARUT - Witantra, Ari Pandu; Khalid, Feldy; Oktaviani, Elfrida (Jurnal Respon Komunitas dan Pemberdayaan, 2025)
This article discusses the role of transformational leadership style in empowering horticultural farmers in Eptilu Cooperative, Garut Regency. Eptilu Cooperative adopts the Closed Loop System concept to ensure the integration of processes from production to marketing. Transformational leadership style, as applied by cooperative leaders, emphasizes clear vision, inspirational motivation, intellectual stimulation, and individual attention. This study used qualitative descriptive methods through interviews and direct observation. The results of the study indicated that transformational leadership significantly increased farmer empowerment in terms of productivity, product quality, technology adoption, and collaboration. The impacts included increased farmer income, cooperative sustainability, and contribution to local food security. This article promoted the importance of transformational leadership in developing an adaptive, innovative, and sustainable agricultural sector.